2019
DOI: 10.1002/aic.16508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating demand response opportunities for power systems resilience using MILP and MINLP Formulations

Abstract: While peak shaving is commonly used to reduce power costs, chemical process facilities that can reduce power consumption on demand during emergencies (e.g., extreme weather events) bring additional value through improved resilience. For process facilities to effectively negotiate demand response (DR) contracts and make investment decisions regarding flexibility, they need to quantify their additional value to the grid. We present a grid‐centric mixed‐integer stochastic programming framework to determine the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To evaluate power interruption time spans of hurricanes, a statistical model is presented in [157]. The authors in [158] propose a mixed-integer stochastic programming framework to measure the worth that chemical facilities can provide to the resilience of the power systems through demand response. In view of the stochastic and sequential properties of events, the prospect effects of events on power system resilience are investigated utilizing sequential Monte Carlo emulations [43].…”
Section: ) Sequential Proactive Operation Strategiesmentioning
confidence: 99%
“…To evaluate power interruption time spans of hurricanes, a statistical model is presented in [157]. The authors in [158] propose a mixed-integer stochastic programming framework to measure the worth that chemical facilities can provide to the resilience of the power systems through demand response. In view of the stochastic and sequential properties of events, the prospect effects of events on power system resilience are investigated utilizing sequential Monte Carlo emulations [43].…”
Section: ) Sequential Proactive Operation Strategiesmentioning
confidence: 99%
“…The authors in [16] suggest co-optimizing transmission line switching and generator redispatch during the recovery stage to minimize load shed following an extreme weather event. Demand response strategies for large industrial customers have also been suggested to aid transmission grid resiliency in [17], where an SOCP relaxation with OTS is used from [18].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…This work considers critical loads and interruptible loads as a demand response program to enhance the resilience of distribution systems after HR events. In Bynum et al (2019) demand response contracts for chemical process facilities in transmission network. In Hafiz et al (2019), a framework for resilient distribution service restoration was presented by considering the integrated control of household flexible appliances to shape the demand curve.…”
Section: Es Operation Cost ($)mentioning
confidence: 99%